Microwave Assisted Synthesis of 4-Phenylquinazolin-2(1H)-one Derivatives that Inhibit Vasopressor Tonus in Rat Thoracic Aorta - Rafaela Teixeira; Talita Menengat; Gabriel Andrade; Bruno Cotrim; Cristiano Ponte; Wilson C. Santos; Gabriel Resende (Molecules, 2020)
Quinazolinones have pharmacological effects on vascular reactivity through different mechanisms. We synthesized 4-phenylquinazolin-2(1H)-one derivatives under microwave irradiation and tested them on the rat thoracic aorta. The prepared compounds 2a−2f were obtained in about 1 h with suitable yields (31−92%). All derivatives produced vasorelaxant effects with IC50 values ranging from 3.41 ± 0.65 µM to 39.72 ± 6.77 µM. Compounds 2c, 2e and 2f demonstrated the highest potency in endothelium-intact aorta rings (IC50 4.31 ± 0.90 µM, 4.94 ± 1.21 µM and 3.41 ± 0.65 µM respectively), and they achieved around 90% relaxation (30 μM). In aorta rings without an endothelium, the effect of compound 2f was abolished. Using the MTT assay to test for cell viability, only compound 2b induced cytotoxicity at the maximum concentration employed (30 µM). The results show that vasorelaxation by 4-phenylquinazolin-2(1H)-one derivatives might depend on the activation of a signalling pathway triggered by endothelium-derived factors.